Desempenho termoenergético da utilização de telhado vegetal em edificação no clima amazônico - MARINHO, Dircirene Tavares (Universidade Federal do Pará, 2017)
The thermoenergetic performance of all construction work stems from the decisionmaking of the initial phase, and the thermo-physical characteristics of the materials used must be considered. The thermo-physical phenomenon of inertia in the roof vegetable offers resistance to the transport of thermic charge to inside the edification, reducing the demand of the electric energy needed to its climatic conditioning. At the same time, the low albedo of the roof vegetable contributes to mitigate the effects of the heat islands in urban environments. The bioclimatic and microclimatic study needed will determine the choice of the suitable construction materials, especially regarding the protection of surfaces exposed to solar heat load. This work deals with the experimental verification of the thermoenergetic performance of a room covered with grass in a place where the vegetation is predominant, in the Parque de Ciência e Tecnologia do Guamá, Campus da Universidade Federal do Pará. The key objective was to examine the thermal response of the slab by proving mitigation of heat spikes by physical phenomenon of thermal inertia, implying favorable results of energy performance by reducing the use of active cooling. It was performed preliminary characterization of the indoor and outdoor microclimate through the obtained values of temperature and relative humidity of air, and observed the evolution of internal environmental conditions in two phases, with the slab discovered and after application of vegetation. The quantitative results showed favorable performance of the roof vegetation in the moderation of heat flow through the slab, contributing to the reduction of the temperature of indoor air and consequent energy efficiency in buildings in Amazonian climate.